2002
DOI: 10.1097/01.mp.0000026054.62220.fc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Duration of Fixation on Quantitative Reverse Transcription Polymerase Chain Reaction Analyses

Abstract: Increasingly, there is the need to analyze gene expression in tumor tissues and correlate these findings with clinical outcome. Because there are few tissue banks containing enough frozen material suitable for large-scale genetic analyses, methods to isolate and quantify messenger RNA (mRNA) from formalin-fixed, paraffin-embedded tissue sections are needed. Recovery of RNA from routinely processed biopsies and quantification by the polymerase chain reaction (PCR) has been reported; however, the effects of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
78
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 31 publications
(37 reference statements)
1
78
0
1
Order By: Relevance
“…All oligonucleotide primers were synthesized by Integrated DNA Technologies (Coralville, IA, USA). Primers for EGFR (Macabeo-Ong et al, 2002), and GAPDH and HMBS primers (Tomlins et al, 2005) were as described previously. The forward primer for ERK1 was 5 0 -CAA CAT GAA GGC CCG AAA CTA CC-3 0 and the reverse primer for ERK1 was 5 0 -TAA CAT CCG GTC CAG CAG GTC A AG-3 0 .…”
Section: Rna Isolation and Quantitative Pcrmentioning
confidence: 99%
“…All oligonucleotide primers were synthesized by Integrated DNA Technologies (Coralville, IA, USA). Primers for EGFR (Macabeo-Ong et al, 2002), and GAPDH and HMBS primers (Tomlins et al, 2005) were as described previously. The forward primer for ERK1 was 5 0 -CAA CAT GAA GGC CCG AAA CTA CC-3 0 and the reverse primer for ERK1 was 5 0 -TAA CAT CCG GTC CAG CAG GTC A AG-3 0 .…”
Section: Rna Isolation and Quantitative Pcrmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18] Moreover, several studies have provided new methods to optimize DNA and RNA extraction from archival formalin-fixed tissues, 18 -25 whereas other studies have investigated the effect of duration of fixation on quantitative RT-PCR analyses. 10,12,13,26 There is a paucity of data in the use of other fixatives that incorporate picric acid (Bouin's solution), or mercuric chloride (B5, Zenker's, Helly's, and Ridley's solutions), or tannic acid as nucleic acid preserving agents. 9,27,28 Only one group of researchers reported that neither DNA nor RNA could successfully be extracted from highly cross-linking fixa-tives such as glutaraldehyde, modified formalins containing mercuric chloride, and Bouin's fixative.…”
mentioning
confidence: 99%
“…Gene expression analyses in FFPE tissues have been largely limited to in situ hybridization or PCR analyses of RNA (Ben-Ezra et al 1991;Nouri Aria et al 1993;Goldsworthy et al 1999;Hayden et al 2001;Lewis et al 2001;Macabeo-Ong et al 2001;Qian et al 2001). Although informative, conventional PCR and in situ hybridization typically evaluate gene expression of only a few genes simultaneously.…”
mentioning
confidence: 99%